Effect of some new generation insecticides on the population abundance of aphid and different beneficial insects in mustard crop (Bangladesh Journal of Agricultural Research, 2017)
The present study evaluated the efficacy of some new generation insecticides namely Clothianidin 48 SC, Fenpyroximate 5 SC, Pyridaben 20 WP and Methoxyphenozide 24 SC along with a synthetic pyrethroid insecticide, Fenpropathrin 20 EC against mustard aphid and their effects on beneficial insects i.e. syrphid flies and foraging honeybees during 2015 - 2016 in Bangladesh Agricultural Research Institute, Gazipur, Bangladesh. Tested six treatments were: Clothianidin 48 SC 1ml l-1, Fenpyroximate 5 SC 0.25 ml l-1, Pyridaben 20 WP 1g l-1, Methoxyphenozide 24 SC 1ml l-1 , Fenpropathrin 20 EC 1ml l-1 and an untreated control, replicated three times in RCBD. It was found that, Methoxyphenozide 24 SC was found to be the most effective against aphid offering lower aphid population (1.42/ top 10 cm central twig) at 7 days after spraying (DAS) which was statistically identical to Clothianidin 48 SC (1.50/top 10 cm central twig). Among the insecticides, Methoxyphenozide 24 SC was also found to be safer to the populations of syrphid flies revealing flight activity of 6.85 adults (plot/5 min) and honeybees of 8.82 workers (plot/5 min), respectively at 7 DAS. Whereas, Clothianidin 48 SC and Pyridaben 25 WP treated plots were found to be highly toxic to these beneficial insects. Consequently, the highest yield was obtained from Methoxyphenozide 24 SC (1.55 t/ha) followed by Fenpyroximate 5 SC (1.42 t/ha) treated plots.Bangladesh J. Agril. Res. 42(3): 563-570, September 2017